EXPLORING THE ESSENCE OF PAKISTANI CULTURE: UNDERSTANDING TAUFIQ RAFAT’S POETRY - Tahir Shah; Aiman Imran; Hifsa Syed; Dr. Abdur Razaq; Bilal Ahmad (International Journal of Contemporary Issues in Social Sciences, 2024)
The research at hand analyzes Taufiq Rafat’s poetry who is one of the most influential Pakistani English writers. It focuses on the ways his works narrate the various aspects of Pakistani culture such as religious, political, economic and nationalistic. The research is delimited to only two of Rafat’s poems, "Arrival of the Monsoon" and "The Kitchens", which are analyzed through the lens of new historicism, using close textual analysis to thoroughly discuss the concept of Pakistaniyat. The approach to the study is exploratory and qualitative in nature which aims to discuss ways in which Rafat’s poetry, deeply ingrained in Pakistani culture, serves his patriotism. The study shows that Rafat’s selected poems are embedded with the themes of nationalism, cultural pride, and a profound love for Pakistan, which makes his works a cornerstone in the representation of Pakistani society in English literature. It further addresses the lack of literature on Taufiq Rafat and other Pakistani poets, which provides an in-depth analysis of his imagery and symbols that capture the cultural and social fabric of Pakistan. It also aims to motivate other researchers to analyze the unique characteristics of Pakistani literature and its place in the global literary landscape.